2018
DOI: 10.1158/1078-0432.ccr-17-1753
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cells with Stem-Like Phenotypes for Diagnosis, Prognosis, and Therapeutic Response Evaluation in Hepatocellular Carcinoma

Abstract: In the present study, we assessed the clinical value of circulating tumor cells (CTC) with stem-like phenotypes for diagnosis, prognosis, and surveillance in hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC) by an optimized qPCR-based detection platform. Differing subsets of CTCs were investigated, and a multimarker diagnostic CTC panel was constructed in a multicenter patient study with independent validation (total = 1,006), including healthy individuals and patients with chronic hepatitis B inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
111
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 38 publications
2
111
0
1
Order By: Relevance
“…Similarly, Schulze et al demonstrated that CTCs were statistically significantly associated with deteriorated survival in patients with intermediate or advanced HCC 26 . We also found that the dynamic changes in the CTC count reflected the treatment efficacy of liver resection for patients with HCC 27,28 . However, to our knowledge, the predictive impact of CTC on EHM in patients with HCC who are undergoing curative surgical resection remains unclear.…”
Section: Introductionsupporting
confidence: 65%
“…Similarly, Schulze et al demonstrated that CTCs were statistically significantly associated with deteriorated survival in patients with intermediate or advanced HCC 26 . We also found that the dynamic changes in the CTC count reflected the treatment efficacy of liver resection for patients with HCC 27,28 . However, to our knowledge, the predictive impact of CTC on EHM in patients with HCC who are undergoing curative surgical resection remains unclear.…”
Section: Introductionsupporting
confidence: 65%
“…At present, the application of CTCs in liver cancer is basically limited to staging, prognosis 40 and therapeutic response evaluation. [41][42][43][44] Protein markers are classic tumuor markers with known stability. In general, good protein markers have considerable advantages in sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…CTCs in patients with HCC are a highly heterogeneous population; currently, there are no widely accepted antigens specifically targeting HCC CTCs [27,63] . Although CellSearch TM system is commonly used in CTC detection, it is reported that the EpCAM-based CTC-sorting strategy could only identify approximately 10%-35% of the total amount of tumor cells in blood due to the EMT process and heterogeneous CTC molecular phenotypes [64,65] .…”
Section: Technology Developed For Detecting Ctc In Hccmentioning
confidence: 99%